URGENSI PELAKSANAAN SUMPAH JABATAN PRESIDEN DAN WAKIL PRESIDEN DALAM PASAL 9 UNDANG-UNDANG DASAR NEGARA REPUBLIK INDONESIA TAHUN 1945 DALAM PERSPEKTIF NEGARA HUKUM DI INDONESIA - Habib Alhuda; Mexsasai Indra; Adi Tiaraputri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Before the President and Vice President are appointed, the implementation of the oath of office is mandatory. Apart from being the basis for the application of the power of a President, the presidential oath is also a juridical indicator to bind a President to be loyal and obedient to the constitution. However, ironically, the oath of office has not been able to have a positive impact in creating good leadership. The President's oath of office is more susceptible to being interpreted as a ceremonial ceremony rather than being interpreted in essence. The absence of limitations and scope of the oath of office norms makes this norm difficult to put into practice. The previous state practice had made the oath of office a political reason to overthrow a President, not a legal reason. Therefore, the oath of office of the President needs serious legal attention in the future. The purpose of this study was to determine the nature and urgency of the implementation of the oath of office as well as the juridical implications that arise when the oath of office is violated in a constitutional perspective in Indonesia.This research is a normative legal research. This is based on library research which takes quotations from reading books, or supporting books that are related to the problem to be studied. This study uses secondary data sources consisting of primary, secondary and tertiary legal materials. This study also uses qualitative data analysis and produces descriptive data.From the results of the research conducted, there are several conclusions obtained, namely: First, the President's oath of office has been identified as an imperative legal norm. The interpretation of the constitution that is carried out, puts the oath of office of the President into real urgency that must be done. The presidential oath of office is also the initial evidence of the effectiveness of the President's power. Second, the President's oath of office can be used as a legal reason to impeach the President when the oath of office is violated. Legal certainty is the rationale for placing the presidential oath of office and has juridical implications when it is violated. Reorienting the oath of office of the President is also necessary in order to strengthen the presidential system itself. The scope and limitations obtained from the oath of office of the President are also implemented so that the norms of the oath of office of the President can be applied consequently. An objective and fair law enforcement must be a necessity in responding to violations of this oath of office.Keywords: Impeachment - Oath of Office - President's Power